Papaya (Carica papaya) leaf methanolic extract modulates in vitro rumen methanogenesis and rumen biohydrogenation - Jafari, Saeid; Goh, Yong Meng; Rajion, Mohamed Ali; Jahromi, Mohammad Faseleh; Ahmad, Yusof; Ebrahimi, Mahdi (Japanese Society of Animal Science, 2017)
Papaya leaf methanolic extract (PLE) at concentrations of 0 (CON), 5 (LLE), 10 (MLE) and 15 (HLE) mg/250 mg dry matter (DM) with 30 mL buffered rumen fluid were incubated for 24 h to identify its effect on in vitro ruminal methanogenesis and ruminal biohydrogenation (BH). Total gas production was not affected (P > 0.05) by addition of PLE compared to the CON at 24 h of incubation. Methane (CH4) production (mL/250 mg DM) decreased (P < 0.05) with increasing levels of PLE. Acetate to propionate ratio was lower (P <0.05) in MLE (2.02) and HLE (1.93) compared to the CON (2.28). Supplementation of the diet with PLE significantly (P <0.05) decreased the rate of BH of C18:1n-9 (oleic acid; OA), C18:2n-6 (linoleic acid; LA), C18:3n-3 (linolenic acid; LNA) and C18 polyunsaturated fatty acids (PUFA) compared to CON after 24 h incubation, which resulted in higher concentrations of BH intermediates such as C18:1 t11 (vaccenic acid; VA), c9t11 conjugated LA (CLA) (rumenic acid; RA) and t10c12 CLA. Real-time PCR analysis indicated that the total bacteria, total protozoa, Butyrivibrio fibrisolvens and methanogen population in HLE decreased (P <0.05) compared to CON, but the total bacteria and B. fibrisolvens population were higher (P < 0.05) in CON compared to the PLE treatment groups.